2016
DOI: 10.1097/bpb.0000000000000304
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous tether of the distal femur produced unilateral genu valgus with subsequent patellar dislocation: case report and review of the literature

Abstract: Fibrous tether at the distal femur is a rare condition that causes angular deformity of the lower extremity; only 18 cases have been reported previously. We report the case of a 2-year-old boy presenting with unilateral genu valgus. The patient had a subsequent lateral patellar dislocation, 1 year after surgical correction. A second surgery was performed to correct this patellar dislocation. Intraoperative finding indicated contracted lateral patellar retinaculum. To the best of our knowledge, this is the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…To date, there have been 23 cases of distal femoral angular deformity caused by FFCD with various treatment methods and outcomes in the literature ( 12 18 ) ( Table 1 ). Thabet et al have reported spontaneous resolution of distal femoral angular deformity in an 18-month-old girl over 7 years of follow-up ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been 23 cases of distal femoral angular deformity caused by FFCD with various treatment methods and outcomes in the literature ( 12 18 ) ( Table 1 ). Thabet et al have reported spontaneous resolution of distal femoral angular deformity in an 18-month-old girl over 7 years of follow-up ( 5 ).…”
Section: Discussionmentioning
confidence: 99%